Wychowanie seksualne a ryzykowne zachowania seksualne młodych dorosłych = Sex education and risk sexual behaviours of young adults - Grabowska, Magdalena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the paper is to present the relationships between three styles of sex education experienced at home and at school, and the tendency of young adults to undertake risk sexual behaviours. In terms of sex education at home the following styles were included: (1) a style based on the openness of interaction, (2) a style based on the lack of openness of interaction and (3) a style based on the openness of interaction within a single sex. And with respect to sex education at school the author adopted the division into frequently described in the literature styles A, B and C. The results of the research lead to a reflection over the factors which influence the formation of sexual behaviour in the context of the development of an individual and widely understood sexual health.
Keywords: style of sex education; home sex education; sex education in schools; sexual risk behaviours; development; sexual health; styl edukacji seksualnej; edukacja seksualna w domu; edukacja seksualna w szkole; ryzykowne zachowania seksualne; rozwój; zdrowie seksualne